Competitive 1T-DRAM in 28 nm FDSOI Technology for Low-Power Embedded Memory - El Dirani, H.; Bawedin, M.; Lee, K.; Parihar, M.; Mescot, X.; Fonteneau, P.; Galy, Ph.; Gamiz, F.; Kim, Y-T.; Ferrari, P.; Cristoloveanu, S. (2016 IEEE SOI-3D-SUBTHRESHOLD MICROELECTRONICS TECHNOLOGY UNIFIED CONFERENCE (S3S), 2016)
We demonstrate experimentally a capacitorless 1T-DRAM fabricated with 28 nm FDSOI. The Z(2)-FET memory cell features a large current sense margin and long retention time at T = 25 degrees C and 85 degrees C. Systematic measurements show that Z(2)-FET exhibits negligible OFF-state current at low drain/gate bias and is suitable as a low-power embedded memory.